Energy consumption and heat island effect mitigation analysis of different roofs considering superposition coupling - Zhao, Shanguo; Zhang, Xiaosong (Frontiers in Energy Research, 2023)
Building energy, particularly air conditioning energy, makes for a significant fraction of overall societal energy usage. The heat island effect is a common urban environmental concern that threatens human sustainable development. Roofs, which cover more than 20% of the total metropolitan area, play an essential role in mitigating the urban heat island effect and lowering building energy use. To examine the triple beneficial benefits of cool roofs and green roofs on building energy conservation in different temperature zones in China, a simulation model based on a typical residential community is established. The results reveal that minimizing direct heat acquisition from the roof, reducing heat transfer from the enclosure, and enhancing the coefficient of performance have a surprising triple effect on building energy saving. In cold areas, hot summer and cold winter areas, and hot summer and warm winter areas, cool roofs may lower the regional ambient temperatures by 2°C, 2.3°C, and 2.6°C, respectively, whereas green roofs can reduce the regional ambient temperatures by 1°C, 1.1°C, and 1.2°C. The triple saving impact of cool roofs and green roofs may accomplish 11.0%, 11.5%, 12.6%, and 9.4%, 8.1%, and 9.3%, respectively, for building energy conservation. Because of the increased solar radiation, cool roofs perform better in low-latitude zones, whereas green roofs function consistently.